Isolasi dan Karakterisasi Senyawa Antibakteri dari Fraksi Etil Asetat Bakteri Bacillus sp.3 (A1) yang Bersimbiosis dengan Spon Laut Haliclona fascigera - Dian Handayani; Rafky Putra; Friardi Ismed (Fakultas Farmasi Universitas Andalas, 2017)
Bacillus sp. 3 is one of symbiotic bacteria of marine sponge Haliclona fascigera obtained from Mandeh Island, Pesisir Selatan, West Sumatra that can produce antibacterial compounds. This study aims to isolate the antibacterial compounds produced by Bacillus sp.3 (A1). The methods that has been used were bacterial cultivation on Nutrient Broth medium using Shaker Incubator at 150 RPM at 37ºC for 48 hours and isolation of antibacterial compound. The isolation method of the compound was carried out by column chromatography method. The testing of antibacterial activity was done by using agar diffusion method. Characterization of isolated compounds were performed using UV and IR spectrophotometer. From this research, two compounds RJ1 and RJ2 were obtained. The compound RJ1 was yellow oily (2.8 mg). The compound RJ1 can inhibit Staphylococcus aureus ATCC 25923 at a 1% of Minimum Inhibition Concentration (KHM). RJ2 compound was yellow oily (3.1 mg). The RJ2 compound can inhibit Escherichia coli ATCC 25922 at a 1% of Minimum Inhibition Concentration (MIC).